Quality Management & Profitability, Issues & Challenges for Algerian Agrifood Companies. - Mezaour , Amel (Milev Journal of Research and Studies, 2020)
The purpose of this research is to analyze the issues and challenges that Algerian agrifood companies face, but also to determine to what extent the quality management applied in them contributes to their profitability.The working methodologie is based on sample surveys on a sample of Algerian agifood companies, for this the survey tool used was the questionnaire that was processed by EXCEL.Our main results are that the benefit of managers with regard to certification is quite positive for Algerian agrifood companies.